Systematic biochemical and cheminformatic evaluation of the gametocytocidal activity of antimalarial lead candidates - Birkholtz, Lyn-Marie (University of Pretoria, 2024)
Thesis (PhD (Biochemistry))--University of Pretoria, 2023.